One-shot Harry - Phillips, Gary, 1955- (Soho Crime, 2022)
"Los Angeles, 1963: African American Korean War veteran Harry Ingram earns a living as a news photographer and occasional process server: chasing police radio calls and dodging baseball bats. With racial tensions running high on the eve of Martin Luther King's Freedom Rally, Ingram risks ending up one of the victims at every crime scene he photographs. When Ingram hears a call over the police scanner to the scene of a deadly automobile accident, he recognizes the vehicle described as belonging to his good friend and old army buddy, the white jazz trumpeter Ben Kingslow, with whom he'd only just reconnected. The LAPD declares the car crash an accident, but when Ingram develops his photos there are signs of foul play. Ingram feels no choice but to play detective, even if it means putting his own life on the line. Armed with his wits, his camera, and occasionally his Colt .45, Harry Ingram plunges head-first into the seamier underbelly of LA society, tangling with racists, leftists, blackmailers, gangsters, zealots and lovers, all in the hope of finding something resembling justice for a friend." --